The personalisation hypothesis in e-learning: Further developments - Yeung, Alexandra; Schmid, Siegbert; Tasker, Roy; King, Michael (UniServe Science, 2008)
Student learning and understanding has the potential to improve with the use of computer-based multimedia environments. Such environments have been expected to offer a powerful effective means of delivering material and enhancing learning (Mayer and Moreno 2002). Presently, there is much research activity investigating best practices for the design of multimedia instructional materials for creating effective e-learning environments. Several principles have already been established and tested such as the multiple representation principle meaning that it is better to present explanations as words and pictures rather than solely words (Mayer and Moreno 2002).